Answer:
r= -9
Explanation:
We are given the equation:
-11 = r+ (-2)
If we want to solve for r, we must isolate r on one side of the equation.
Let's simplify the right side. A + - can just be written as -
-11= r-2
2 is being subtracted from r. The inverse of subtraction is addition. Add 2 to both sides of the equation.
-11 + 2= r-2+2
-11+2=r
-9=r
r=-9
Let's check our solution. Plug -9 in for r and solve.
-11= -9 + (-2)
-11= -11
This checks out, so we know our solution is correct.
The solution to the equation -11=r+(-2) is r=-9